Clinical and laboratory predictors of Infectious Complications in patients after Out-of-Hospital Cardiac Arrest - Kroupa, Josef; Knot, Jiri; Ulman, Jaroslav; Bednar, Frantisek; Dohnalova, Alena; Motovska, Zuzana (Journal of critical care, 2017)
PURPOSE: Identification of clinical and laboratory predictors related to Infectious Complications (ICs) in patients after Out-of-Hospital Cardiac Arrest (OHCA). METHODS: Patients, aged >18, after an OHCA between 9/2013 and 11/2015, surviving >24h, were studied. RESULTS: Study group consisted of 42 patients (mean age 63.4years, 88.1% men). Forty percent of patients had IC; lower respiratory tract infections were most common (87.5% of cases). ICs were more common in patients receiving Targeted Temperature Management (50% vs. 10%; p=0.032). Antibiotics were used in 85.7% of patients. The mean time to therapy initiation was 9.6 (SD 7.1) hours after admission. The mean course of treatment was 9.0 (SD 6.2) days. Fifty-three percent of patients receiving early antibiotic treatment didn't have IC. Initial antibiotic therapy was changed more often in patients with IC (75% vs. 38.9%; p=0.045). C-Reactive Protein, Procalcitonin, Troponin and White Blood Cell count values were higher in patients with IC. CONCLUSION: Early initiated antibiotic treatment is overused in patients after OHCA. This practice is associated with necessitating antibiotic change in the majority of patients with IC. Assessment of clinical and laboratory parameters in the first days after OHCA increases the likelihood of appropriate ATB therapy.
Keywords: infekce dýchací soustavy; umělé dýchání; Female; urgentní služby nemocnice; Hypothermia, Induced; C-Reactive Protein; ženské pohlaví; Calcitonin; sepse; Out-of-Hospital Cardiac Arrest; Sepsis; ST Elevation Myocardial Infarction; lidé; Unnecessary Procedures; terapeutická hypotermie; Anti-Bacterial Agents; infarkt myokardu s elevacemi ST úseků; antibiotická profylaxe; Respiratory Tract Infections; zástava srdce mimo nemocnici; délka pobytu; Length of Stay; Coronary Care Units; Emergency Service, Hospital; koronární jednotky; Male; Time-to-Treatment; čas zasáhnout při rozvinutí nemoci; lidé středního věku; C-reaktivní protein; kalcitonin; mužské pohlaví; antibakteriální látky; procedury zbytečné; Respiration, Artificial; Middle Aged; Antibiotic Prophylaxis; Humans